2020
DOI: 10.1099/ijsem.0.004004
|View full text |Cite
|
Sign up to set email alerts
|

Description of Paenibacillus tepidiphilus sp. nov., isolated from a tepid spring

Abstract: China is a hotspot for hot springs and during microbial diversity analysis of Tengchong hot spring, Yunnan province, south-west PR China, two strains designated SYSU G01001T and SY-13 were isolated. SYSU G01001T and SY-13 were Gram-stain-positive, motile and spore-forming. Colonies were white, circular, raised and punctiform. SYSU G01001T and SY-13 grew at pH 6.0–9.0 (optimum pH 8.0) and at 23–37 °C (optimum 28 °C). The 16S rRNA gene sequence similarity between SYSU G01001T and SY-13 was 99.6 % but these strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Growth was determined at various temperatures (20, 30, 40, 50, 60 and 70 °C) and pH levels (pH 5.0, 6.0, 7.0, 8.0, 9.0, and 10.0). The pH of the PCA medium was adjusted using the buffer system described by Narsing Rao et al [30]. Tolerance to NaCl was tested on International Streptomyces Project 2 agar at concentrations of 1–10 % (w/v).…”
Section: Full-textmentioning
confidence: 99%
“…Growth was determined at various temperatures (20, 30, 40, 50, 60 and 70 °C) and pH levels (pH 5.0, 6.0, 7.0, 8.0, 9.0, and 10.0). The pH of the PCA medium was adjusted using the buffer system described by Narsing Rao et al [30]. Tolerance to NaCl was tested on International Streptomyces Project 2 agar at concentrations of 1–10 % (w/v).…”
Section: Full-textmentioning
confidence: 99%
“…Genomic DNA extraction and 16S rRNA gene amplification, purification, cloning and sequencing of the raw sequence was carried out as described previously [15]. The obtained sequence was compared with the 16S rRNA gene sequences of species with validly published species in EzBioCloud server (www.ezbiocloud.net) [16].…”
Section: Full-textmentioning
confidence: 99%
“…It indicated that the bacterial strain investigated in this study formed a distinct monophyletic clade from the genus Paenibacillus . Strain S150 T shared low sequence similarity with the type strains of: P. jilunlii Be17 GQ985393 T (97.5%) [14], P. sonchi X19-5 T DQ358736 (97.2%) [15], P. tepidiphilus SYSU G01001 T (96.7%) [16], suggesting that strain S150 T should be classified as a novel species in the genus Paenibacillus .…”
Section: Figurementioning
confidence: 99%